Application of Project Based Learning Model on Basic Chemical Colloidal Materials to Improve Science Process Skills and Student Learning Outcomes - Minarni Minarni; Epinur Epinur; Fuldiaratman Fuldiaratman; Yusnidar Yusnidar; Rizalia Wardiah (Budapest International Research and Critics University, 2022)
The old view, learning as a process of interaction between lecturers and students in the context of knowledge transfer. Along with the times with the era of sophisticated technology and globalization, the concept is no longer appropriate. In this era of technology and globalization, the challenges of life are increasingly complex. Student centered learning must be interactive, fun, challenging, motivate students to participate actively, and provide sufficient space for initiative, creativity, and independence in accordance with the talents, interests, and physical and psychological development of students. From the various existing learning models, innovation can choose project-based learning model. Students constructively carry out deepening learning with a research-based approach to weighty, real, and relevant problems and questions. Science process skills are important skills to be used in the science learning process such as in studying chemistry. In addition, science process skills also reflect the behavior of scientists in classifying science, but the current science process skills of students are still low. The purpose of this study is to analyze application of project-based learning model on basic chemical colloidal materials to improve science process skills and student learning outcomes. The research area was carried out in the Chemical Education Study Program, PMIPAFKIP, Universitas Jambi in the odd semester 2021/2022. The population in the study were all students who contracted Basic Chemistry II in the odd semester of the 2021/2022 academic year. The sample was taken in one class. This research is a quantitative study using a pre-experimental design type one group pretest-posttest (single group initial-test-posttest). The results showed that project-based learning model can be applied to basic chemical colloidal materials. Students' science process skills in learning colloidal materials by applying project-based learning model are very good. Student learning outcomes in learning basic chemical colloidal materials by applying project-based learning model are very good.